Consortial shared print archiving: perspectives from Canada. Issue 1 (13th January 2014) - Bird, Gwen; Wong, Sabrina
Abstract : Purpose: – This paper aims to present a Canadian perspective on consortial shared print programs among research libraries. Design/methodology/approach: – This paper includes a brief environmental scan of shared print initiatives in Canada and the USA, as well as briefly mentioning shared print programs in Australia, New Zealand, the UK and Hong Kong. The Shared Print Archive Network of the Council of Prairie and Pacific University Libraries in western Canada is used as a case study, to highlight the challenges and opportunities of shared print initiatives. Findings: – The importance of a suitably streamlined governance structure for cooperative shared print projects is discussed. The challenge of national coordination in countries where there is no national policy or program is contrasted with those countries having national coordination of shared print or centralized repositories. The challenge of assessing the impact and effectiveness of shared print programs is also discussed. Originality/value: – Cooperation between shared print initiatives in different regions will help bring about a culture change in collections management, from operating in isolated silos to open sharing of expertise and practices.